Standard of living of oil palm small holders in Beaufort, Sabah / Adrian Sylvester Molius ... [et al.] - Molius, Adrian Sylvester; Chua, Esther; Sigutil, Nora; M Fathil Ibrahim, Rosnilah (2003)
The purpose of this research is to survey the standard of living of oil palm small holders in Beaufort, Sabah. Standard of living/quality of life is a broad perspective. Therefore, the scope of this research will only encompasses mainly on the earnings of the small holders and the few type of assets own by them. The need for the study arose as the government has been emphasizing agriculture sector to uplift the standard of living of the 'Rakyat' in particular those in rural areas. Malaysia is the largest producer of oil palm in the world with Sabah being the largest state's producer of oil palm with acreage of plantation of 1.65 million hectares as at year '2004. Therefore, being the state's largest producer of oil palm, we felt that there is a need to actually gauge the small holders standard of living as they are mainly comprises of people in the rural areas. Our research objective will outline the following :-